DEVELOPMENT OF READY-TO-EAT COOKIES FROM GEO SPECIFIC ANCHOVY (STELOPHORUS HETEROLOBUS) FORTIFIED WITH PUMPKIN SEED FLOUR - D. BHAGYA, (The Journal of Research ANGRAU, 2025)
The purpose of this study carried out in 2022-2023 was to develop and assess the sensory  and nutrient characteristics of pumpkin seed flour fortified anchovy-based (Stelophorus heterolobus) cookies. The results showed that addition of pumpkin seed flour at a ratio of 30 percent and anchovy powder 10 percent did not change the consistency or flavour of cookies and enhanced the nutritive value. Fortified anchovy cookies were found to provide calorie (1256.8kcal), carbohydrate (74.63g), protein (19.13g) and fat (42.2g) per 100 grams. The fibre content of cookies was found to be 10.49g as pumpkin seed flour and wheat flour are rich in fibre. The calcium, iron, and vitamin C content of the sample were 116.63mg, 4.72mg, and 15.64mg respectively.Microbial analysis of cookies revealed that it was safe for human consumption in terms of E. coli with Total Plate Count of